Structural Glaciology of a Glacier Confluence, Kaskawulsh Glacier, Yukon Territory, Canada - Anderton, Peter W. (Research Foundation and the Institute of Polar Studies, The Ohio State University., 1973)
The study is part of the program of the Icefield Ranges Research Project, which is operated jointly by the American Geographical Society and the Arctic Institute of North America. The University Archives has determined that this item is of continuing value to OSU's history. A study was made of the deformation of the surface ice at the confluence of the north and central arms of the Kaskawulsh Glacier with particular reference to the relationship between optic-axis fabrics of the ice and deformation. Measurements of surface velocity made in the confluence area along transverse profiles show a progressive change from independent profiles across each arm toward a unified profile across the combined system. These velocity profiles show no evidence of discrete shear between the north and central arms. Strain-rate measurements near the point of confluence show that the surface ice flows through a changing stress field equivalent to simple shear with an increasing component of transverse compression. The transverse compression becomes dominant close to the median line and is associated with longitudinal extension parallel to the median line. Longitudinal foliation defined by near-vertical layers of clear and bubbly ice is present in ice near the point of confluence. Toward the median line the bubbles in the ice are increasingly flattened in the plane of layering and are elongated downglacier. Many of the clear layers contain fine-grained ice, fractures, or zones of cataclasis and are presumably active zones of concentrated shearing. Other clear layers which are not associated with distinctive textural features are probably passively deforming recrystallized structures. The optic-axis fabrics of both types of clear layers are, however, similar to the fabrics of adjacent bubbly layers. In ice subjected to high strain rates (> l0-4/day), the optic-axis fabrics are symmetrically related to the directions of the principal strain rates. Most of these fabric patterns are approximately centered on a direction of maximum shearing strain rate, but the fabric patterns in the ice closest to the median line are centered on the direction of principal compressive strain rate. Fabric patterns are not consistently related to the pole to the foliation, c. All the fabrics seem to be imposed rather than inherited fabrics. In ice subjected to low strain rates (< l0-4/day), the optic-axis fabrics are not symmetrically related to the directions of the principal strain rates or to the pole to the foliation, c. These fabrics are as strongly developed as those in areas of high strain rates and may be inherited from upglacier.